SLANG LANGUAGE IN SOLIDIFYING IDENTITY AND SOLIDARITY: A SOCIOLINGUISTIC ANALYSIS OF THE EPISODE 'DUELING HATS' FROM THE COMEDY SKETCH 'KEY & PEELE' - Abdussalam Jabaruddin Yamjirin; Henry Yustanto; Wiwik Yulianti (INJOSEDU: International Journal of Social and Education, 2025)
This study examines the use of African-American slang in the episode "Dueling Hats" from the comedy sketch Key & Peele, which aired on July 16, 2009. The research aims to understand the function and meaning of slang usage in social communication, particularly as a marker of identity and solidarity within the African-American community. The method used is a qualitative descriptive analysis with Miles and Huberman's (1992) data analysis techniques, involving data reduction, data presentation, and drawing conclusions/verification. The analysis results show that slang in dialogue not only functions as everyday communication tools but also as strong cultural identity symbols. The use of words like "yo," "cuz," and "dog" reflects closeness and solidarity, reducing social and emotional distance between individuals. Slang also enables more efficient and rapid communication. The use of slang in this context creates a special communication code that reinforces a sense of membership and togetherness within the African- American community. This study contributes to understanding the complexity and richness of African-American culture through slang, as well as highlighting the importance of language in forming and maintaining social relationships. The findings are expected to enhance insights in sociolinguistics and media analysis studies.